2017
DOI: 10.1136/bmj.j84
|View full text |Cite
|
Sign up to set email alerts
|

Association between continuity of care in general practice and hospital admissions for ambulatory care sensitive conditions: cross sectional study of routinely collected, person level data

Abstract: ObjeCtiveTo assess whether continuity of care with a general practitioner is associated with hospital admissions for ambulatory care sensitive conditions for older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
306
6
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(342 citation statements)
references
References 28 publications
15
306
6
15
Order By: Relevance
“…The study of Barker et al 10 was one of the first in the United Kingdom to link continuity of care and number of hospital admissions using individual-level data. Our study used individual-level longitudinal data, allowing a stronger basis for inferring a causal relationship between continuity of care and first emergency hospital admission between April 2012 and March 2014.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The study of Barker et al 10 was one of the first in the United Kingdom to link continuity of care and number of hospital admissions using individual-level data. Our study used individual-level longitudinal data, allowing a stronger basis for inferring a causal relationship between continuity of care and first emergency hospital admission between April 2012 and March 2014.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Salisbury et al 8 focused on multimorbidity and continuity of care, while Ridd et al 9 focused on continuity and diagnosis of cancer, but neither included acute care. Barker et al 10 found an association between higher continuity of care and fewer admissions for ambulatory care-sensitive conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Angesichts der Bedeutungszunahme chronisch behandlungsbedürftiger Krankheiten und fortschreitender Spezialisierung in der Medizin wird in den meisten Gesundheitssystemen nach Wegen zur Verbesserung der Kooperation und Koordination der Behandlungsprozesse gesucht [6] Der Gedanke lässt sich auch auf das deutsche Gesundheitssystem übertragen, in dem Patienten größte Wahlfreiheiten genießen. Nicht zuletzt aufgrund der hohen Zahl von Arztkontakten [7,8] sowie der zunehmenden Krankenhausaufnahmen ohne ärztliche Einweisung (vgl.…”
Section: Dominik Von Stillfried · Tatiana Ermakova · Frank Ng · Thomaunclassified
“…For example, there is evidence in primary care that continuity of care in general practice is linked to improved outcomes such as prevention of secondary care admissions (Barker et al . ) and continuity of care is also associated with heightened patient satisfaction in systematic reviews of the literature (Adler et al . ).…”
Section: Discussionmentioning
confidence: 99%